2017
DOI: 10.4314/bajopas.v10i1.16
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic effect of ethanol leaf extract of <i>Combretum micranthum</i> blood glucose and oxidative stress biomarkers on alloxan induced diabetic in wistar rats

Abstract: This research was aimed to investigate the anti micranthum on blood glucose levels and oxidative stress biomarkers such as malondaldehyde, superoxide dismutase, catalase and glutathione peroxidase on alloxan induced Diabetes in Wistar rats. Diabetes was induced using alloxan (150 mg/kg i.p). The rats w rats each. Group 1 served as the diabetic control, Group 2 received 2 mg/kg glibenclamide, while Groups 3, 4 and 5 were orally administered 100, 200 and 400 mg/kg body weight of ethanol leaf extract of Combretum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…However, we were unable to assign the P. nudicaule CYP719 into a subfamily, as it did not have a CYP719 subfamily sequence matching higher than 40%. CYP80 and CYP719 were specifically involved in the biosynthesis of berberine, and those species used in the phylogenetic analysis were all berberine-producing medicinal plants, except C. micranthum, which has been used as a medicinal plant and contains various phytochemicals, including alkaloids [ 49 ]. However, its alkaloids were not further characterized.…”
Section: Discussionmentioning
confidence: 99%
“…However, we were unable to assign the P. nudicaule CYP719 into a subfamily, as it did not have a CYP719 subfamily sequence matching higher than 40%. CYP80 and CYP719 were specifically involved in the biosynthesis of berberine, and those species used in the phylogenetic analysis were all berberine-producing medicinal plants, except C. micranthum, which has been used as a medicinal plant and contains various phytochemicals, including alkaloids [ 49 ]. However, its alkaloids were not further characterized.…”
Section: Discussionmentioning
confidence: 99%
“…There was also a significant decrease (p<0.05) in oxidative stress biomarkers compared to the diabetic control. C. micranthum reduced blood sugar, reactive oxygen free radicals, and improved antioxidant enzyme activities [65] …”
Section: Pharmacological Activitiesmentioning
confidence: 96%
“…C. micranthum reduced blood sugar, reactive oxygen free radicals, and improved antioxidant enzyme activities. [65] Ononamadu et al (2021) identified potential antidiabetic compounds from active subfractions of C. micranthum extracts using in silico techniques. The results validated the antidiabetic potential of the extract and some of the identified compounds exhibiting high binding affinity with the target proteins compared to the reference drug (acarbose).…”
Section: Antidiabetic Activitymentioning
confidence: 99%
“…The antioxidant properties of Abelmoschus esculentus have been revealed by previous research [ 83 , 84 , 85 , 86 ], and this is attributable mainly to its active compounds, such as polyphenols and flavonoids [ 87 ] ( Figure 3 ). Polyphenols mediate antioxidant activity by reducing MDA and increasing SOD, GPx, and catalase activity [ 77 , 78 , 82 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ]. Some of the active polyphenol compounds include isoquercetin, quercetin, quercetin-3-O-gentiobioside, quercetin-3-O-glucoside, protocatechuic acid, and rutin.…”
Section: Abelmoschus Esculentusmentioning
confidence: 99%
“…However, due to reduced CAT activity, beta cells of the pancreas that contain many mitochondria undergo oxidative stress by producing excess ROS that leads to β-cells dysfunction and, ultimately, diabetes [ 18 ]. Interestingly, evidence presented in Table 2 showed that Abelmoschus esculentus treatment in rodent models of diabetes significantly increases CAT activity [ 91 , 95 , 105 , 106 , 113 , 115 , 117 ]. This suggests that Abelmoschus esculentus may ameliorate oxidative stress, further reduce complications of DM, or prevent DM in non-diabetics ( Figure 4 ).…”
Section: Abelmoschus Esculentusmentioning
confidence: 99%